1981
DOI: 10.1002/bbpc.19810850917
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen Reduction on Transition‐Metal Porphyrins in Acid Electrolyte I. Activity

Abstract: The oxygen reduction characteristics of metalloporphyrins adsorbed at monolayer levels on a high surface area carbon, Norit BRX, have been studied in 8 N H,SO, and also in 6 N KOH. In an acid, oxygen reduction activity is found to be correlated with the Me"/Me"' redox potential. Most Co complexes have too high a redox potential, while too low a redox potential is observed for Fe, Ru, Os, Mn, and Cr. Ir porphyrins have the highest activity. In KOH, Ru porphyrins show the best performance. A heat treatment impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
7

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(44 citation statements)
references
References 53 publications
5
32
0
7
Order By: Relevance
“…In contrast, for cobalt macrocyclics reduction of O 2 starts at potentials much more negative than those corresponding to the Co(III)/Co(II) couple [366]. Several authors have reported correlations between activity (measured as potential at constant current) and the M(III)/M(II) formal potential and volcano-shaped curves have been obtained [13,366,384,385]. This could indicate that the redox potential needs to be located in an appropriate rather narrow window to achieve maximum activity as discussed before for the oxidation of thiols.…”
Section: Interaction Of O 2 With Active Sites and The Redox Mechanismmentioning
confidence: 83%
See 1 more Smart Citation
“…In contrast, for cobalt macrocyclics reduction of O 2 starts at potentials much more negative than those corresponding to the Co(III)/Co(II) couple [366]. Several authors have reported correlations between activity (measured as potential at constant current) and the M(III)/M(II) formal potential and volcano-shaped curves have been obtained [13,366,384,385]. This could indicate that the redox potential needs to be located in an appropriate rather narrow window to achieve maximum activity as discussed before for the oxidation of thiols.…”
Section: Interaction Of O 2 With Active Sites and The Redox Mechanismmentioning
confidence: 83%
“…The low activity of Cr and Mn can be attributed to their low redox potential, i.e. they are easily oxidized [14,385]. Most macrocyclic metal complexes increase their activity after heat treatment [361].…”
Section: Two To Four-electron Reduction Catalysts For the Reduction Omentioning
confidence: 99%
“…These catalysts suffered from low ORR activity and stability in the ORR regime and are, thus, far from satisfying the requirements for their application in commercial fuel cells. Subsequently, in the 1970s, pyrolysis of metal-N 4 macrocycles adsorbed on carbon black in inert atmosphere was discovered to significantly improve the ORR activity as well as the stability [12][13][14][15][16][17] of the catalyst. It is proposed in the literature that, upon pyrolysis, the metal-N4 macrocycle molecules decompose, resulting in the catalysts containing the M-N 4 type of active sites to be embedded on the carbon support [18].…”
Section: Mnc-based Catalyst Obtained Through Pyrolysismentioning
confidence: 99%
“…As a function of the central transition metal in the phthalocyanine complex (MPc), van Veen found that the order of activity for oxygen reduction in both acid and base is: Fe > Co Ru > Mn > Pd Pt > Zn [4]. This result has lead to the almost exclusive study of the FePc and CoPc complexes in acid and alkaline aqueous solutions [5,6]. However, the stability of these firstrow complexes is not high under operating conditions, especially in acidic electrolytes, and this has frustrated attempts to use their excellent electrocatalytic properties to sustain competitive current densities.…”
Section: Introductionmentioning
confidence: 95%